A highly potent and stable pan-coronavirus fusion inhibitor as a candidate prophylactic and therapeutic for COVID-19 and other coronavirus diseases - Jie Zhou; Wei Xu; Zezhong Liu; Chao Wang; Shuai Xia; Qiaoshuai Lan; Yanxing Cai; Shan Su; Jing Pu; Lixiao Xing; Youhua Xie; Lu Lu; et al. (Elsevier, 2022)
The development of broad-spectrum antivirals against human coronaviruses (HCoVs) is critical to combat the current coronavirus disease 2019 (COVID-19) pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and its variants, as well as future outbreaks of emerging CoVs. We have previously identified a polyethylene glycol-conjugated (PEGylated) lipopeptide, EK1C4, with potent pan-CoV fusion inhibitory activity. However, PEG linkers in peptide or protein drugs may reduce stability or induce anti-PEG antibodies in vivo. Therefore, we herein report the design and synthesis of a series of dePEGylated lipopeptide-based pan-CoV fusion inhibitors featuring the replacement of the PEG linker with amino acids in the heptad repeat 2 C-terminal fragment (HR2-CF) of HCoV-OC43. Among these lipopeptides, EKL1C showed the most potent inhibitory activity against infection by SARS-CoV-2 and its spike (S) mutants, as well as other HCoVs and some bat SARS-related coronaviruses (SARSr-CoVs) tested. The dePEGylated lipopeptide EKL1C exhibited significantly stronger resistance to proteolytic enzymes, better metabolic stability in mouse serum, higher thermostability than the PEGylated lipopeptide EK1C4, suggesting that EKL1C could be further developed as a candidate prophylactic and therapeutic for COVID-19 and other coronavirus diseases.